The Effect Of Perception Of Organizational Support And Employee Engagement On Employee Performance With Job Satisfaction As An Mediation In The Personnel Affairs And Human Resource Development Agency Of Cilegon City - Sri Yulyaningtias; Ahmad Mukhlis; Udin Suadma (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study is based on the phenomenon of declining employee performance, which is often influenced by internal and external organizational factors, such as suboptimal organizational support, suboptimal levels of work engagement, and varying levels of job satisfaction. Employee performance is a crucial factor in supporting the successful achievement of an agency's goals, so it is necessary to analyze the factors that can drive its improvement. The purpose of this study is to strengthen previous empirical findings and provide academic contributions regarding the relationships between variables in the context of public sector organizations. In addition to this primary objective, this study aims to determine the significance of perceived organizational support, job engagement, and job satisfaction on performance. This study employed quantitative methods as its research design. Data were collected through questionnaires distributed to employees working in the Department of Personnel and Human Resource Development. The data were then analyzed using a Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS). Hypothesis testing was conducted through construct validity and reliability evaluation, as well as path coefficient analysis to determine the relationships between variables. The research findings indicate that increased job satisfaction is positively and significantly correlated with employee performance. Furthermore, perceived organizational support has been shown to positively impact job satisfaction levels, which in turn plays a role in indirectly driving performance improvement. Meanwhile, job engagement has a significant influence on employee performance, but does not show a significant relationship with job satisfaction, so this variable does not function as a mediator in the relationship between job engagement and performance. Overall, these results confirm the importance of job satisfaction and organizational support as key determinants in improving employee performance. The conclusion of this study confirms that employee performance can be improved through job satisfaction derived from adequate organizational support. While work engagement does impact performance, it is not strong enough to increase job satisfaction. Therefore, organizations need to strengthen tangible support for employees and improve job satisfaction management strategies to drive sustainable productivity and performance.